TRANSLATION PROBLEMS OF THE POSTMODERN LITERARY TEXT - Lashchenko, K.G. (Proceedings of National Aviation University (archive), 2005)
The article reviews general problems of the postmodern fiction translation. The author discusses interrelation between required cognitive base of a translator, appropriate translation skills and excellent knowledge of native language on one hand, and adequate translation of postmodern fiction on the other hand. Translator’s difficulties generated by the literary work specifics are analyzed and summarized, and practical ways to curb with them are suggested.